Reach and predictors of effects during nation-wide dissemination of the universal parenting program All Children in Focus - Livia van Leuven; Johanna Engelbrektsson; Martin Forster (BMC, 2023)
Abstract Background Parenting programs have the potential to improve population health, if widely disseminated. However, wide-scale dissemination is challenging. Also, more knowledge is needed of whether parenting programs are effective for the variability of families in the general population. Methods This study aimed to investigate who the universal parenting program All Children in Focus (ABC) reaches when offered in routine care in Sweden. A second aim was to investigate if the outcomes were predicted by factors related to family background, group leader experience, and homework completion. Questionnaires were collected before and after ABC from 1420 parents. Hierarchical regression analyses were performed to examine predictors of disruptive child behavior, parenting practices, and satisfaction. Results ABC was available in about 40% of Swedish municipalities and reached a fairly representative population sample, with the exception that fewer fathers than mothers participated. The examined predictors explained a small proportion of the variance in the outcomes (2.5, 3.5 and 14.7%, respectively). Still, the effect on disruptive child behavior was statistically significantly larger for parents born in Sweden, with higher education, and older children. The effect on parenting practices was also larger for parents born in Sweden, for mothers, and for those practicing homework more frequently. Most examined predictors showed no statistically significant association with child and parenting outcomes. Parents were generally satisfied with ABC and the significant predictors of satisfaction had little practical meaning. Conclusions A fairly representative group of parents across Sweden were reached by ABC. Background variables, homework completion, and group leaders' experience explained a small proportion of variance in the outcomes. Meanwhile, the slightly lower intervention effects found for preschool children and parents born abroad calls for further investigation, since even small differences in effects can have an impact at a population level. The study also points to the importance of stressing homework completion and to increase the reach of universal parenting interventions to some underrepresented groups.